OMOTENASHI: BUDAYA KERAMAHTAMAHAN DI JEPANG (AKAR BUDAYA DAN MANIFESTASINYA) - Lina Rosliana (KIRYOKU, 2018)
(Title: Omotenashi: Hospitality Culture in Japan, Its Culture’s Root and Manifestacy) When visiting Japan, we will be able to feel the true meaning of the slogan "Guest is King". Even if we live for seven years, we will still be amazed by the hospitality given by the Japanese, both for tourists, foreigners who live, to the Japanese people themselves. Then what if we can't go to Japan and feel the hospitality right away? Have products made by Japan. There is no need for large products like electronic devices or Japanese cars, but enough to see, for example snacks that are produced directly in Japan. Instantly we will feel that inanimate objects can also provide 'red carpet service'. The principle embedded in Japanese people when giving hospitality to guests or consumers should not be formed. How it is formed, and what it looks like, needs to be examined to create an understanding of the need for a hospitality culture in society, and the great effects that can be created by a country that maintains a hospitality culture. This research is a qualitative descriptive study. The researcher tries to describe in depth the roots of hospitality culture in Japan and how the culture is manifested by Japanese society. This research model raised specific issues, namely focusing only on Japanese hospitality culture by describing data that is able to represent phenomena in depth.